2012
DOI: 10.1007/s00468-012-0799-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of simulated acid rain stress on a staple forest plant, Pinus massoniana Lamb: a proteomic analysis

Abstract: At present, acid rain has become one of the top ten global environmental issues. Acid rain causes slower growth, injury, or decline of forests. Some dramatic effects on forests have been observed in south China since the late 1970s and the situation is deteriorating. We carried out a comparative proteomic analysis on Pinus massoniana Lamb, a staple tree species widely distributed in middle and south China to gain a better understanding of tree response to acid rain at molecular level. Two-year-old P. massonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 58 publications
1
20
0
1
Order By: Relevance
“…This indicated that ATP synthesis activity is enhanced, likely because plants need an increased energy production to deal with NH4 + toxicity. Similar observations have been reported in wheat (Wang et al, 2008b) and potato (Aghaei et al, 2008) under saline stress and Masson's pine under acid rain stress (Wang et al, 2013), indicating that sustained ATP synthesis is a common strategy for as plants under stress.…”
Section: Discussionsupporting
confidence: 83%
“…This indicated that ATP synthesis activity is enhanced, likely because plants need an increased energy production to deal with NH4 + toxicity. Similar observations have been reported in wheat (Wang et al, 2008b) and potato (Aghaei et al, 2008) under saline stress and Masson's pine under acid rain stress (Wang et al, 2013), indicating that sustained ATP synthesis is a common strategy for as plants under stress.…”
Section: Discussionsupporting
confidence: 83%
“…In the plant kingdom, woody species are found within both Angiosperms and Gymnosperms. On the Gymnosperm group, much research has been conducted on the genus Pinus (Wu et al 2008;Valledor et al 20082010;Wang et al 2013), with Maritime pine ( Pinus pinaster Ait.) being one of the most representative species used for reforestation in South-western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Acid rain caused by high SO 2 and NO x concentration could bring serious negative effects on ecosystems (soil and water PH value change, crops plants injury, etc.) (Jalali and Naderi, 2012;Wang et al, 2013). In addition, air pollution could also reduce the atmospheric visibility and change the climate (Ramana et al, 2010;Langridge et al, 2012).…”
Section: Introductionmentioning
confidence: 99%